Dinamika Konflik Dan Adaptasi Pedagang Keliling Dalam Masyarakat Modern: Perspektif Sosiologi Konflik Dahrendorf - Deandra Rafiq Daffa; Dave Arthuro (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The journal 'The Dynamics of Conflict and Adaptation of Mobile Traders in Modern Society: A Dahrendorf Conflict Sociological Perspective' explores the complex interactions between mobile traders and modern society using the sociological framework of conflict proposed by Ralf Dahrendorf. This research details how mobile merchants, as social groups vulnerable to conflict with existing social authorities and structures, seek to adapt in a modern society filled with diverse social, economic, and cultural changes. With a focus on the dynamics of conflicts that arise along their journey, this journal also analyzes the adaptation strategies used by mobile traders in answering the challenges faced in this modern era. Through Dahrendorf's approach, this journal provides an in-depth insight into social change and conflict that occurs in contemporary society, by focusing on the role and experience of mobile traders as social agents who interact in the complexity of conflict and adaptation structures.